Pendampingan Pengembangan Lidah Buaya menjadi Berbagai Olahan dan Produk Kesehatan sebagai Branding Keunggulan SMK Muhammadiyah 2 Turi - Agus Nugroho Setiawan; Septi Nur Wijayanti; Anisa Dwi Makrufi (WARTA LPM, 2021)
SMK Muhammadiyah 2 Turi (SMKM 2 Turi) has launched a program for developing Aloe vera as an excellent branding. The development of aloe vera at SMKM 2 Turi has started but the results have not been optimal, due to limited knowledge, insight, and skills of most students and teachers of SMKM 2 Turi, as well as the limited supporting facilities. This community service was conducted to increase the knowledge and skills of teachers and students of SMKM 2 Turi in the development of aloe vera, as well as assistance in the cultivation and processing of crops. Community service programs were conducted using several methods, including community education, science, and technology diffusion, facilitation, consultation, and mentoring. With assistance and guidance from the UMY Team, the development of aloe vera cultivation and processing at SMK Muhammadiyah 2 Turi has been carried out quite well, with the result that the population of aloe vera has increased to 2 times the population and various kinds of processed products of drinks, snacks, and health products. These aloe products are used for internal school purposes or Muhammadiyah activities at various events and are sold to the public market because they already have a PIRT license. This activity is not only able to make the school environment more conducive, but it also provides benefits as a learning medium, especially entrepreneurship for students and teachers, and is expected to be an excellent branding for SMK Muhammadiyah 2 Turi.